2021
DOI: 10.15537/smj.2021.42.3.20200814
|View full text |Cite
|
Sign up to set email alerts
|

Pathological spectrum of endometrial biopsies in Saudi women with abnormal uterine bleeding

Abstract: To assess and age stratify the types and frequencies of endometrial pathologies in Saudi women with abnormal uterine bleeding (AUB) that underwent endometrial biopsies, at our hospital over a 13-year period. Methods: In a retrospective study, from 2006 to 2018, all endometrial biopsies from Saudi women with AUB, reported at the laboratory of King Saud University-Medical City, Riyadh, Saudi Arabia, were revisited and analyzed. The women were categorized into <40, between 40-55 and >55 years of age. Original Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…Endometrial cancer or malignant diagnosis in AUBs increases with increasing age and is more common in the postmenopausal period [18]. When the literature is examined, it is seen that women diagnosed with malignancy are in the postmenopausal period or over 50 years of age [3,12,16,18]. This result is consistent with the literature and in our study, 11 of 20 women diagnosed with malignancy were found to be in the postmenopausal period.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Endometrial cancer or malignant diagnosis in AUBs increases with increasing age and is more common in the postmenopausal period [18]. When the literature is examined, it is seen that women diagnosed with malignancy are in the postmenopausal period or over 50 years of age [3,12,16,18]. This result is consistent with the literature and in our study, 11 of 20 women diagnosed with malignancy were found to be in the postmenopausal period.…”
Section: Discussionsupporting
confidence: 92%
“…Women presenting with OCD anywhere in the premenopausal or postmenopausal period should be closely evaluated for cancer incidence [6,[13][14][15]. When the literature was examined, it was seen that women who came with the complaint of AUB were diagnosed with endometrial cancer in the range of 6.2-15.2% [10,[15][16][17][18]. In the studies in our country, this rate was found to be between 0.3-5% [3,6,12].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations